2017
DOI: 10.1111/jan.13448
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the waiting area as perceived by haemodialysis patients and family carers

Abstract: This study contributes to a better understanding of the distinct culture experienced by haemodialysis patients in the waiting area and the findings can help nurses deliver more meaningful care. Nursing interventions germane to psychological and emotional support and applicable nursing education should be seriously considered for haemodialysis waiting rooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This finding was consistent with a study conducted in Nigeria [ 18 ] whereas a study conducted in New Zealand [ 24 ] contradicted this result where there is a provision of in-home service and satellite dialysis centers. Also, long procedure times (3-4 hours) were mentioned as a challenge in this study and supported by studies conducted in South Korea [ 25 ], New Zealand [ 24 ], and Australia [ 26 ].…”
Section: Discussionmentioning
confidence: 62%
“…This finding was consistent with a study conducted in Nigeria [ 18 ] whereas a study conducted in New Zealand [ 24 ] contradicted this result where there is a provision of in-home service and satellite dialysis centers. Also, long procedure times (3-4 hours) were mentioned as a challenge in this study and supported by studies conducted in South Korea [ 25 ], New Zealand [ 24 ], and Australia [ 26 ].…”
Section: Discussionmentioning
confidence: 62%
“…K. Hall, Cary et al 2020;R. Hall, Rutledge et al 2020;Kim et al, 2018;Lin et al, 2005). A range of emotions were expressed such as sadness and suffering (R. K. Hall, Cary et al, 2020;R.…”
Section: Spiritual and Existential Needsmentioning
confidence: 99%
“…According to Hashemi et al (2018), poor infection control procedures and a lack of medical attention were perceived to be the cause of their chronic illness and the reason as to why patients viewed their health as poor (Kim et al, 2018). Carers and family members felt obligated to remain with their loved one when receiving HD as they did not feel they were being properly looked after by health professionals (Kim et al, 2018). Interestingly, only one study found the delivery of care was adequate, supportive, and organised and that health professionals were considered motivating and encouraging regarding their health (Jhamb et al, 2016).…”
Section: Service Improvementsmentioning
confidence: 99%
“…Because of this compulsory togetherness, it stands to reason that patients receiving in-center HD may form relationships with one another, and prior research has in fact documented that this does happen. [1][2][3] It also stands to reason that when a patient falls ill during a session or is absent from the center-either temporarily or permanently-it could affect fellow patients. Data describing how often a patient becomes sick enough during HD to require transport from the center to the hospital are unavailable, but the most serious event that could complicate HD, a cardiac arrest, is estimated to occur at a rate of 1 per 142 patient-years in the United States (US).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this compulsory togetherness, it stands to reason that patients receiving in‐center HD may form relationships with one another, and prior research has in fact documented that this does happen 1‐3 . It also stands to reason that when a patient falls ill during a session or is absent from the center—either temporarily or permanently—it could affect fellow patients.…”
Section: Introductionmentioning
confidence: 99%